2020
DOI: 10.1038/s41598-020-58594-3
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamics mixed type urinary incontinence with advanced pelvic organ prolapse, management and outcomes

Abstract: patients with pelvic organ prolapse (pop) often have accompanying lower urinary tract symptoms. Symptoms such as stress urinary incontinence(SUi-UD) and detrusor overactivty(Do) would co-exist in a number of patients. Management entails relieving the obstructive element. to determine the clinical outcome of patients with urodynamics mixed type urinary incontinence(MUi-U) after vaginal pelvic reconstructive surgery(PRS), a retrospective study was conducted. MUI-U was defined as having urodynamic findings of bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Theoretically, artificial repair can improve or even cure pelvic floor dysfunction. In addition, relevant studies suggest that POP and SUI have similar etiology and pathogenesis, and the two often coexist [ 23 , 24 ]. Therefore, concurrent anti-SUI is the key to treating POP.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, artificial repair can improve or even cure pelvic floor dysfunction. In addition, relevant studies suggest that POP and SUI have similar etiology and pathogenesis, and the two often coexist [ 23 , 24 ]. Therefore, concurrent anti-SUI is the key to treating POP.…”
Section: Discussionmentioning
confidence: 99%
“…Only 2 patients had resolution of symptoms while 4 patients remained to be suffering from such, since restoration of the anatomical defect can only provide 56% objective cure. 25…”
Section: Discussionmentioning
confidence: 99%
“…These symptoms may be due to the urethra being obstructed preoperatively due to the severe prolapse of the organ, which has squeezed and distorted the urethra. Some patients also present with insidious stress incontinence, which gradually becomes apparent after pelvic floor reconstruction due to a change in the urethral angle ( 24 , 25 ). In this study, two new cases of lower urinary tract symptoms of varying degrees were found in the T4 group during the postoperative follow-up period, while no new symptoms were found in the mSSLF group.…”
Section: Discussionmentioning
confidence: 99%